Research on Performance of Scroll Compressor and System under Suction Injection - Yin Xiang; Sun Shuaihui; Cao Feng; Shu Pengcheng (Zhileng xuebao)
In order to analyze the relationship between the suction injection and the performance of the scroll compressor, the suction injection circuit was set up. And the mathematic model, containing the loss of leakage and heat exchange, was established at the same time. The discharge temperature and the refrigerating capacity and the COP of the system were investigated when the injection flow rate and the pressure ratio were varied. The result of the simulation was in reasonable agreement with the experimental data. The error was 2.5% at the low injection flow, and 10% at the high flow. It was also found that the discharge temperature decreased and the COP slightly increased then went down, when the injection flow increased. The COP of the system increased by 0.6%, while the discharge temperature decreased by 14 ℃ at the condition of the low injection flow. When the discharge temperature decreased by 42 ℃, the decline in the COP was less than 5%. Additionally, there existed an optimal value of the COP in the suction injection circuit when the injection flow varied at the high pressure ratio. Furthermore, the higher the pressure ratio was, the lower the COP decreased. As a result, the suction injection could put into use to decrease the discharge temperature.